Starter diet for Asian seabass larvae - Mohd Shahidin, Syafiqah Hanani; Mohammad Noor, Normawaty; Mohd Idris, Shaharah; Mustafa, Sufian; Mukai, Yukinori (2019)
Seed production of marine finfish in Malaysia is still facing problem particularly live feed for starter diet. Currently, aqua culturists use S or SS type rotifers, which have sizes from 100 to 200μm. Early stage larvae of some marine finfish species select feeds less than 100 μm. Protozoa is a collective term of aquatic microorganism that has been identified to be suitable live feed, as their body sizes are less than 100μm. Thus, the objective of this experiment is to compare the survival rates of Asian seabass larvae using four types of live feeds. Four types of live feed; rotifer, protozoa, E. encysticus, and mixed (rotifer, protozoa, and E. encysticus) were used in this experiment. The larvae were fed from 2 to 10 day-after-hatching. Asian seabass larvae were given the same amount of live feed in each larval rearing tank; twice a day. The feeding densities were 20 individual / mL for rotifers, protozoa, E. encysticus, and mixed group. Number of seabass larvae in each group was counted every day and their survival rates were determined. Starting from 3 DAH until 10 DAH, mixed group showed the higher survival rates than other groups. The most recommended live feed was mixed group.